A study on impingement heat transfer characteristics of partially premixed flames on double-concentric-pipe burner. (15th January 2021) - Zhen, H.S.; Wang, Z.W.; Liu, X.Y.; Wei, Z.L.; Leung, C.W.; Huang, Z.H.
Abstract: This paper presents an experimental study of free flame patterns, impinging flame structures and flame impingement heat transfer characteristics of a partially premixed flame. The partially premixed flame is produced on a double-concentric-pipe burner, with both flow strength and mixedness of its inner and outer jets controlled by digital flowmeters. The aim of the study is, through examination of the effects of inner and outer jet Reynolds numbers ( Re i, Re o ), equivalence ratios ( Φ i, Φ o ) and nozzle-to-plate distance ( H ), to understand the heat transfer behaviors of such partially premixed flame and further identify the best impinging flame to achieve higher energy usage efficiency. A total of twelve different free flame patterns are observed by varying Re i - Re o - Φ i - Φ o, and W-shaped flame is the most representative flame under the conditions tested. The partially premixed dual flame is higher in stability than any single component of it, i.e. Bunsen flame or annulus flame. Further, leaner flammability limit is achieved by the dual flame due to mutual interaction which effectively supports leaner inner flame. Both inner and outer flames influence the radial heat flux distribution of W flame, while the contribution of inner flame becomes significant only when the difference in two flame heights is large. The outer flame globally dominates the total heat transfer rate, leading to general decay with increasing H . Comparison of W flame with single Bunsen and annulus flame shows that W flame has the favorable structure for higher energy efficiency due to double-pipe configuration and mutual flame interaction.